2006
DOI: 10.1111/j.1574-6968.1997.tb10329.x
|View full text |Cite
|
Sign up to set email alerts
|

Sterols and fatty acids of different Aspergillus species

Abstract: Sterol and fatty acid composition were combined for comparison of five industrially important Aspergillus species. Quantitative amounts of individual fatty acids, especially unsaturated ones, and the composition of sterols showed the differences among fungi examined. Besides ergosterol, six other sterols were present in detectable amounts in fungal mycelia. The most outstanding were the differences in the amounts of linolenic acid, ergosterol, and lanosterol, as well as in a sterol with M+376 identified as erg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 18 publications
(17 reference statements)
0
10
3
1
Order By: Relevance
“…Eight types were represented the most, with palmitic acid, estearic acid, oleic acid, and linoleic acid as the most abundant, whereas palmitoleic acid margaric acid, linoleic acid and araquidic acid were detected in smaller ratios among the six evaluated species. These results were not in agreement with Nemec et al (1997), who investigated the FA profiles of A. flavus and A. fumigatus. They reported that palmitic acid, palmitolelic acid, margaric acid, estearic acid, oleic acid, linoleic acid and linolenic acid were prevalent and araquidic acid was not found.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Eight types were represented the most, with palmitic acid, estearic acid, oleic acid, and linoleic acid as the most abundant, whereas palmitoleic acid margaric acid, linoleic acid and araquidic acid were detected in smaller ratios among the six evaluated species. These results were not in agreement with Nemec et al (1997), who investigated the FA profiles of A. flavus and A. fumigatus. They reported that palmitic acid, palmitolelic acid, margaric acid, estearic acid, oleic acid, linoleic acid and linolenic acid were prevalent and araquidic acid was not found.…”
Section: Discussioncontrasting
confidence: 54%
“…The number of FA obtained in this work was higher than the ones obtained for different fungal species reported by Blomquist et al (1992), Stahl and Klug (1996) and Nemec et al (1997). The capillary column length (100 m) probably favored the fungal biomass FA detection in comparison to the 20 mL capillary columns used in other studies (Blomquist et al 1992, Müller et al 1994, Nemec et al 1997, Stahl & Klug 1996, Silva et al 1998.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations